CROWDFUNDING: DEMOKRATISASI AKSES KEUANGAN DALAM MENDUKUNG AKSI SOSIAL MAHASISWA - Fauzi Abdillah; Endang Danial (Jurnal Ilmiah Mimbar Demokrasi, 2015)
The purpose of this study were to explore how crowdfunding can support social action both online and offline movement of students. Eighteen participants consisting of crowdfunding platform founder, founder and volunteer organization participated in this study. Grounded theory methodology was applied and involved simultaneous data collection, coding and analysis through constant comparison. The emerging theory is â€œdemocratization financial accessâ€.